2012
DOI: 10.1002/path.3978
|View full text |Cite
|
Sign up to set email alerts
|

Central role of lactic acidosis in cancer cell resistance to glucose deprivation‐induced cell death

Abstract: Solid tumours are dependent on glucose, but are generally glucose-deprived due to poor vascularization. Nevertheless, cancer cells can generally survive glucose deprivation better than their normal counterparts. Thus, to render cancer cells sensitive to glucose depletion may potentially provide an effective strategy for cancer intervention. We propose that lactic acidosis, a tumour microenvironment factor, may allow cancer cells to develop resistance to glucose deprivation-induced death, and that disruption of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
101
3
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(112 citation statements)
references
References 57 publications
6
101
3
2
Order By: Relevance
“…Glucose deprivation also induces autophagy [71]. In response to changes in AMP and ADP concentrations in the setting of glucose deprivation, AMPK is activated by LKB1.…”
Section: Autophagy and Metabolic Stress In Cancermentioning
confidence: 99%
“…Glucose deprivation also induces autophagy [71]. In response to changes in AMP and ADP concentrations in the setting of glucose deprivation, AMPK is activated by LKB1.…”
Section: Autophagy and Metabolic Stress In Cancermentioning
confidence: 99%
“…A previous study found that lactate could also induce hypoxia signaling to promote cell growth and angiogenesis [12]. Lactate was also reported to facilitate cell survival in an unfavorable environment [13].…”
Section: Introductionmentioning
confidence: 99%
“…This was not only evident in chronically hypoxic areas, where hyperthermia decreased the amount of quiescent cells considerably, but was also detectable in the total tumour cell population [76]. In addition, re-oxygenation induces microenvironmental changes, such as decreased acidosis and induces cell cycle arrest, resulting in autophagy and eventually apoptosis [105].…”
Section: Hypoxiamentioning
confidence: 95%